2021
DOI: 10.1038/s41598-021-02672-7
|View full text |Cite
|
Sign up to set email alerts
|

Associations between parent–child relationship, and children’s externalizing and internalizing symptoms, and lifestyle behaviors in China during the COVID-19 epidemic

Abstract: To investigate associations between parent–child relationships, children’s externalizing and internalizing symptoms, and lifestyle responses to the COVID-19 epidemic, we conducted an online survey of a random, representative sample of residents with children aged 3–17 years during mid-March 2020 in Wuhan and Shanghai, China. A total of 1655 parents and children were surveyed with a response rate of 80.1% in the survey. During the epidemic, the frequency of children enquiring about the epidemic (AOR = 1.46, 95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 30 publications
(38 reference statements)
0
19
1
1
Order By: Relevance
“…In our study 34% had emotional 31% had conduct and 17% had hyperactivity symptoms respectively during the COVID-19 pandemic. In a similar study found that a small proportion of children (8.0%, 65/816 in Wuhan and 11.7%, 98/839 in Shanghai) had a substantial risk of clinically significant emotional problems which is lower prevalence than our study and 39.5% of children in Wuhan and 58.4% in Shanghai had behavioral problems such as aggressive or stubborn behavior and tantrums or meltdowns during the epidemic (p < 0.001) which is higher than our study [7]. This result is slightly different because in our study the sample size is smaller and our study conducted in one area whereas the other study conducted in two big cities with large sample.…”
Section: Discussioncontrasting
confidence: 86%
“…In our study 34% had emotional 31% had conduct and 17% had hyperactivity symptoms respectively during the COVID-19 pandemic. In a similar study found that a small proportion of children (8.0%, 65/816 in Wuhan and 11.7%, 98/839 in Shanghai) had a substantial risk of clinically significant emotional problems which is lower prevalence than our study and 39.5% of children in Wuhan and 58.4% in Shanghai had behavioral problems such as aggressive or stubborn behavior and tantrums or meltdowns during the epidemic (p < 0.001) which is higher than our study [7]. This result is slightly different because in our study the sample size is smaller and our study conducted in one area whereas the other study conducted in two big cities with large sample.…”
Section: Discussioncontrasting
confidence: 86%
“…However, higher levels of stress and the changing work environments during COVID-19 may have negatively influenced how parents interacted with their children. It has been shown that COVID-19 associated with higher levels of parental emotional abuse ( Chung et al, 2020 ; Du et al, 2021 ) , and changing work environments and schedules may have altered how parents monitored their children during the pandemic ( Chung et al, 2020 ; Du et al, 2021 ; Chen and Harris, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since COVID-19 has spread around the world, vulnerable groups such as low-income families and adolescents have been more exposed to difficulties ( 26 , 34 ). Given that low-income students might not have sufficient support for development of self-efficacy compared to those in middle or high economic classes, it is necessary to pay more attention to development of their self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, family satisfaction is related to self-efficacy ( 28 30 ), and this was confirmed in the current study, particularly among adolescents in low-income families. However, parents in low-income households might be busier and more exhausted in workplace since COVID-19 because an economic recession has made it more challenging to make money and be employed, particularly for low-income families ( 26 ). Unstable wages and job insecurity might interrupt communication or cohesion among or satisfaction with family members ( 27 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation